Measurement of the electron temperature in dielectric barrier discharge by line-ratio method of optical emission spectroscopy - Tyata, R.B.; Subedi, D.P.; Wong, C.S. (Journal of Science and Engineering, 2015)
In this paper, experimental results of atmospheric pressure dielectric barrier discharge (DBD) produced in air and nitrogen gas have been presented. The discharge was generated using a high voltage (0-20 kV) power supply operating at 10-30 kHz in hemispherical electrodes system with dielectric barrier of glass between the electrodes. Optical emission spectroscopy was used for the characterization of the discharge produced at atmospheric pressure. The emission spectra in the range of 200 nm to 450 nm have been analyzed to estimate the electron temperature by line intensity ratio method. The results show that the electron temperature is about 0.70 eV in air and 0.71 in nitrogen.